Environmental issues of agro-tourism: the views of coastal community in Malaysia - Muhammad, Mahazan; Hamzah, Azimi; Md. Yassin, Sulaiman; Abu Samah, Bahaman; Tiraieyari, Neda; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2016)
Tourism industry was growing rapidly in Malaysia and has been important contributor to the economy. Many types of tourism industry have been created in Malaysia since it has a unique culture and natural beauty as a tourist attraction. Agro-tourism in coastal villages is one of the new product of tourism to stimulate economic growth in rural community especially among fishermen community. This type of agro-tourism use the environment for tourism resources. Hence, this study is concerned with the environmental impacts of agro-tourism activities in coastal villages listed as Desa Wawasan Nelayan in Malaysia. This is a quantitative study where data were gained through developed questionnaires. Sampling was conducted in 10 fishermen villages in peninsular Malaysia. Finding in this study indicates that the environments of the coastal community in fishermen villages are still natural, protected and not be a negative issue due to the deterioration of agro-tourism program.